Plant Oxidative Stress: Biology, Physiology and Mitigation (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, “Plant Oxidative Stress: Biology, Physiology, and Mitigation”, published 11 original research works and 1 review article that discussed the various aspects of ROS Biology, metabolism, and the physiological mechanisms and approaches to mitigating oxidative stress. These types of research studies show further directions for the development of crop plants that are tolerant to abiotic stress in the era of climate change.